Updated list of fleas (Insecta: Siphonaptera) of the Korean Peninsula, with the presence of Rhadinopsylla alphabetica Jameson & Sakaguti in the Democratic People’s Republic of Korea - Keskin, Adem; Beaucournu, Jean-Claude (Zootaxa, 2020)
During the re-examination of some specimens in the Siphonaptera collection of J.-C. Beaucournu, we noticed unidentified Rhadinopsylla specimens. After the detailed comparison, they were identified as Rhadinopsylla alphabetica Jameson & Sakaguti. These specimens of R. alphabetica were collected from Grey Red-backed Vole, Myodes rufocanus (Sundevall), in Ryanggang province of the Democratic People’s Republic of Korea (DPRK). To the best of our knowledge, this is the first report of R. alphabetica in the DPRK. Our specimens of R. alphabetica have some minor differences from Alaskan and Japanese populations. To draw attention to these differences we also provide detailed drawings of R. alphabetica specimens in the present study. The information on the flea fauna of the Korean peninsula is very fragmentary and articles on fleas of the Korean peninsula have been published in different languages. Therefore, it is very difficult to find accessible and updated flea list of the Korean peninsula for the scientific community. Based on the published and accessible literature, we provide a list of 45 flea taxa from the Korean peninsula.